2021
DOI: 10.1111/1462-2920.15753
|View full text |Cite|
|
Sign up to set email alerts
|

Endosomal sorting complexes required for transport‐0 (ESCRT‐0) are essential for fungal development, pathogenicity, autophagy and ER‐phagy in Magnaporthe oryzae

Abstract: Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT-0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT-0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae. Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
(104 reference statements)
0
18
0
Order By: Relevance
“…Previously, we identified ESCRT-0 complex, and showed that its two components Δ Movps27 and Δ Mohse1 participated in fungal development, pathogenicity, autophagy, and ER-phagy in M. oryzae ( Sun et al, 2021 ). In this study, we focused on MoIst1, a subunit of ESCRT III to explore its function in M. oryzae .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we identified ESCRT-0 complex, and showed that its two components Δ Movps27 and Δ Mohse1 participated in fungal development, pathogenicity, autophagy, and ER-phagy in M. oryzae ( Sun et al, 2021 ). In this study, we focused on MoIst1, a subunit of ESCRT III to explore its function in M. oryzae .…”
Section: Resultsmentioning
confidence: 99%
“…The integrity of the cell wall, which is the first barrier contacting the external environment, plays a crucial role in the homeostasis of M. oryzae [ 28 ]. To assess the role of MoNAP1 in cell wall integrity stress, the growth of the wild-type 70-15, ∆ Monap1 and Monap1c strains was measured in CM with three cell wall integrity stresses, including 75 μg mL −1 calcofluor white (CFW), 600 μg mL −1 Congo red (CR), and 0.004% sodium dodecyl sulfate (SDS) ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, ∆ Monap1 was sensitive to two chitin-binding anionic dyes, CFW and CR, which inhibited the assembly of enzymes that connect chitin to (1-3)-β-glucan and (1-6)-β-glucan [ 52 ], indicating that the loss of MoNAP1 affects the CWI pathway. The CWI pathway controls the cellular remodeling process in response to environmental challenges in fungi [ 28 , 52 ]. Bleomycin (BLM) is a DNA-damaging agent that acts by not only inducing DNA strand breaks [ 53 ] but also destroying cell wall components through oxidation and preventing the formation of fungal septum and cytokinesis [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of PHF23 promoted autophagosome synthesis ( 60 ). Both enhanced and attenuated autophagy resulted in impaired virulence of M. oryzae ( 16 , 20 , 75 77 ). Therefore, we speculate that Clp1 affects the development and pathogenicity of M. oryzae in two ways: one is to regulate autophagy homeostasis by interacting with autophagy-related proteins at PAS and autophagosomes, and the other is to regulate gene transcription in the nucleus.…”
Section: Discussionmentioning
confidence: 99%